Answer:
Option C x=2, y=6
Explanation:
we know that
The hypotenuse leg theorem, (HL theorem), states that if the hypotenuse and one leg of a right triangle are congruent to the hypotenuse and one leg of another right triangle, then the triangles are congruent
so
In this problem
Equate the hypotenuses of both right triangles
x+3=y-1 -----> x=y-4 ------> equation A
Equate the legs of both right triangles
y-3=2x-1 ----> equation B
substitute equation A in equation B and solve for y
y-3=2(y-4)-1
y-3=2y-8-1
2y-y=-3+9
y=6
Find the value of x
x=y-4 ------> x=6-4=2
therefore
x=2, y=6